Mobile health interventions: A policymakers' note on the World's largest Nutrition Surveillance in India - Sumantra Pal (ZBW - Leibniz Information Centre for Economics, 2022)
India's first-generation and short-lived nutrition surveillance pilot (called ICDS-CAS) launched in 2018 was dismantled and replaced by a second-generation program (called POSHAN 2.0) in 2021. To estimate the relative effectiveness of 18 services provided by the frontline workers using ICDA-CAS, I approach its geographically phased-out pilot as a natural experiment, exploiting the quasi-random district-level assignment of ICDS-CAS and interventions. I access the publicly unavailable telephonic survey data collected during spring 2021 from the World Bank. It covers 1100 pregnant women and 3300 lactating mothers in 124 randomly sampled districts from 11 populous Indian states. I find that the adherence to recommended iron supplementation is 33 percentage points higher for pregnant women, who received information, messages, and counselling from the frontline health workers in districts which implemented ICDS-CAS. For lactating mothers, who attended a village health and nutrition day event, the impact on iron supplementation is 9 percentage points greater if they were residing in ICDS-CAS districts. The data suggests that the remaining interventions are not effective. Feature comparison of both the programs suggests that India's second-generation nutrition surveillance is more diligently designed than its predecessor, hence more promising. – – El piloto de vigilancia nutricional de primera generación y corta duración de la India (llamado ICDS-CAS) lanzado en 2018 fue desmantelado y reemplazado por un programa de segunda generación (llamado POSHAN 2.0) en 2021. Para estimar la efectividad relativa de 18 servicios proporcionados por la primera línea trabajadores que usan ICDA-CAS, abordo su piloto geográficamente eliminado como un experimento natural, explotando la asignación casi aleatoria a nivel de distrito de ICDS-CAS e intervenciones. Accedo a los datos de la encuesta telefónica no disponibles públicamente recopilados durante la primavera de 2021 del Banco Mundial. Cubre 1100 mujeres embarazadas y 3300 madres lactantes en 124 distritos seleccionados al azar de 11 estados indios populosos. Encuentro que la adherencia a la suplementación de hierro recomendada es 33 puntos porcentuales más alta para las mujeres embarazadas, quienes recibieron información, mensajes y asesoramiento de los trabajadores de salud de primera línea en los distritos que implementaron ICDS-CAS. Para las madres lactantes que asistieron a un evento del día de salud y nutrición de la aldea, el impacto en la suplementación con hierro es 9 puntos porcentuales mayor si residían en los distritos ICDS-CAS. Los datos sugieren que las intervenciones restantes no son efectivas. La comparación de características de ambos programas sugiere que la vigilancia nutricional de segunda generación de la India está dise\~nada con más diligencia que su predecesora, por lo tanto, es más prometedora.
Keywords: I120; I150; 330; maternal health; service delivery; mobile phones; India